Mathematics and Raka'at of Dhuha Prayer - Monika Monika; Irni Latifa Irsal; Fakhruddin Fakhruddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The uniqueness of the number raka’at of dhuha prayers taught by the Prophet gave new interest to the author to see the relationship of the number of raka'ah of the dhuha prayer with Mathematics. The non-interactive qualitative approach of the Library Research type is a research method to explore mathematical interconnections and the number of rak'ahs of the dhuha prayer. There are four steps in this research, namely data collection, data reduction, data presentation, and data analysis. Descriptive analysis is used to present the results of the interconnection between mathematics and the number of rak'ahs of the dhuha prayer. In this study, expert validation was carried out to ensure the validity of the data and the results of the analysis. From the research, it was found that the number of rak'ahs for the dhuha prayer, when written in one line, will form the same pattern as the integer pattern. The general form of the pattern of the number of rak'ahs for the dhuha prayer that is formed Un = 2n.